Multiple Sclerosis (M.S.): Epidemiologic Research in 187 Patients Who Admitted in University Cnters of Tehran in 1998 - Homeira Sajjadi (University of Social Welfare and Rehabilitation Sciences, 2001)
Objective: Multiple Sclerosis (M.S.) is a chronic disease which most commonly involves females. Prevalence of disease begins from adolescent, gradually increases until 35 years old and then decreases. Its geographical distribution is non homogen and prevalence changes from 5/100000 to 250/100000. Iran is a low incident region with prevalence of 5/100000 or at least 3000 patients. Materials & Methods: This research has been done on 187 patients who admitted in Tehran university centers in 1998. Results: Results show that 63.3% of patients were female and most of them were married. The average age at beginning was 28y. Conclusion: Manifestation of disease were: Extremity weakness (44.2%), vision cloudiness and diplopia (33.7%) and sensory disturbances (32.2%).